Changing patterns in attempted suicides: experience from a tertiary care hospital in Sri Lanka. (1st March 2011) - de Silva, P; de Silva, D; Jayasinghe, S; de Alwis Seneviratne, R; Abeyratne, M; Rajapakse, D; Mendis, N
Abstract : Objectives: To describe characteristics of patients admitted to National Hospital Sri Lanka (NHSL) following attempted suicide. Methods: Trained researchers identified all patients admitted following attempted suicide to NHSL from April 2002 to April 2003. A pretested questionnaire was used to collect relevant information. Results: Of 1067 cases, 593 (55.6%) were females, 183 (61%) were less than 24 years of age, 609 (57.8%) single, 845 (83.9%) had received up to secondary education, and 448 (44.9%) were in full time employment. Mean duration of admission was 82.38 h. Case death rate was 4.6% (49 deaths). There were 965 (91.8%) deliberate self-poisoning among which 316 (30.1%) ingested pesticides; 222 (21.1%) non-opioid analgesics, antipyretics and antirheumatics, 130 (12.4%) other drugs, 135 (12.8%) other noxious substances. Substances used in self-poisoning were 197 (20.4%) Paracetamol, 126 (13%) Run-rat, 41 (4.2%) Kerosene oil and 39 (4%) Diazepam. Two hundred and three (30%) were referred for psychiatric care and none to police. Conclusion: Substances used for attempted suicide have changed, with an increased use of medicines, in contrast to organophosphates reported as commonest substance in 1976. Paracetamol has emerged commonest substance and necessitates policies for minimising access to substance, along with developing guide-lines for management. A change in referral pattern was seen. An audit of records in 1994 indicated 90% of persons were referred to police, while in this study police referral was not observed and follows decriminalisation of attempted suicides.